The phytolith assemblage - Powers, Alix (Scottish Archaeological Internet Reports, 2003)
This study demonstrates that areas of ancient human occupation and activity are characterised by concentration of phytoliths which are orders of magnitude higher than occur naturally in coastal dune systems. Some aspects of human activity can be distinguished, ie the introduction of peat, turves, plant or animal waste and possible differences in pasture/grazing in the area.